PENGARUH MODEL PROBLEM BASED LEARNING TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS PESERTA DIDIK KELAS XI SMK NEGERI 1 BATIPUH - Rukiah, Siti (Departemen Matematika, 2024)
An important skill in mastering mathematics is the ability to solve mathematical problems. Grade XI students at SMK Negeri 1 Batipuh still have this ability, although in a poor form. The application of the Problem Based Learning (PBL) model can be used as a way to improve it. The purpose of this study was to characterise the growth of learners' problem-solving skills in mathematics as they progress through PBL and conventional models. A quasi-experiment with nonequivalent posttest-only control group is the core of this study. The sample was class XI TITL 1 and XI TKR 1 at SMK Negeri 1 Batipuh in FY 2024/2025 by simple randomisation. The evaluation tools used were quizzes and final tests. Grade XI students at SMK Negeri 1 Batipuh outperformed their peers in the conventional learning model when using the PBL methodology. In addition, compared to the average quiz results at each meeting, individuals using PBL experienced significant improvement.Keywords– Mathematical Problem Solving Ability, Problem Based Learning, Conventional Model Learning